Degradation of Pinus sylvestris and Populus tremula by laccate Ganoderma species - Cortina-Escribano, Marta; Barbero-López, Aitor; Kilpeläinen, Petri; Vanhanen, Henri; Haapala, Antti (De Gruyter, 2024)
Wood chips and sawdust are used for cultivating Ganoderma lucidum mushrooms. In Northern Europe, side-streams of Pinus sylvestris are highly abundant, however as cultivation substrate they inhibit the growth of G. lucidum. To identify the changes in lignocellulosic composition after fungal degradation, the major lignocellulosic components in P. sylvestris and an optimal substrate for G. lucidum, Populus tremula were analyzed. Populus tremula was evenly degraded while the glucan fraction of P. sylvestris was not degraded and its lignin fraction was consumed almost completely. Despite not being an optimal substrate, P. sylvestris was successfully delignified by G. lucidum.
Keywords: softwood; biomass valorization; fungal decay; mushroom cultivation; mushroom substrate; wood composition